The Role of Investors' Protection On The Relationship Between International Financial Reporting Standards Implementation And Earnings Response Coefficient Of Listed Companies In Nigeria - Sunny Biobele Beredugo (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
This study was interested in unraveling the efficacy of investors’ protection on earnings response in an IFRS environment. This is because investors still consider information on investors’ protection besides earnings in taking their decisions. Yet, this rare variable is usually treated with laxity in the firms’ annual reports. The study assessed the interactive effects between IFRS provisions and investors' protection on the Earnings Response Coefficient of listed companies in Nigerian. This study adopted historical-descriptive research design and content analysis research designs. This was conducted using forty six listed companies in Nigerian covering the period of 6 years (2013 to 2018). The data of the study was analyzed using the Partial Least Square. It was discovered that ERC improves with the moderating effect of strong investors’ protection in an IFRS environment. It is therefore recommended that firms listed in the Nigerian stock exchange should as a result of necessity improve on their investors' protection in order to promote a high earnings response coefficient under an IFRS environment